Leadership in Action : Face to Face - Presence of Mind - A Conversation with Tony Buzan - Rush, Stephen (Center for Creative Leadership, 2002)
Tony Buzan is a leading authority on the brain and techniques of thinking and learning. More than forty years ago he developed Mind Maps®, a powerful graphical and visualization tool designed to unlock the brain's potential.